2012
DOI: 10.1007/s00005-012-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 Antitrypsin: A Potent Anti-Inflammatory and Potential Novel Therapeutic Agent

Abstract: Alpha-1 antitrypsin (AAT) has long been thought of as an important anti-protease in the lung where it is known to decrease the destructive effects of major proteases such as neutrophil elastase. In recent years, the perception of this protein in this simple one dimensional capacity as an anti-protease has evolved and it is now recognised that AAT has significant anti-inflammatory properties affecting a wide range of inflammatory cells, leading to its potential therapeutic use in a number of important diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 167 publications
(154 reference statements)
3
101
0
1
Order By: Relevance
“…Thus, inhibition of NE has consistently been the objective in the development of therapeutic strategies for these patients. However, the broad anti-inflammatory and immunomodulating properties of AAT (7,8,23) raise the question whether elastase inhibition accounts for the spectrum of biological activities of AAT. Here, we compared in vitro and in vivo anti-inflammatory effects of clinical grade AAT with elastase inhibitory activity to a form of recombinant AAT that does not inhibit elastase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibition of NE has consistently been the objective in the development of therapeutic strategies for these patients. However, the broad anti-inflammatory and immunomodulating properties of AAT (7,8,23) raise the question whether elastase inhibition accounts for the spectrum of biological activities of AAT. Here, we compared in vitro and in vivo anti-inflammatory effects of clinical grade AAT with elastase inhibitory activity to a form of recombinant AAT that does not inhibit elastase.…”
Section: Discussionmentioning
confidence: 99%
“…However, aside from its primary role as an antiprotease, AAT has gained attention due to emerging evidence of its ability to exert a range of immunomodulatory properties affecting a number of immune and structural cells of the airways (71). Studies have shown that native AAT may modulate immune cell function of neutrophils (72)(73)(74)(75), monocytes (71,76), and T cells (77), and the results of this study are analogous to data demonstrating the inhibitory effect of AAT on IL-8-and TNF-a-induced neutrophil responses (28,29). Moreover, this study elucidates what we think to be a novel role for AAT and has uncovered the ability of AAT to inhibit adhesion and degranulation signaling events involving AAT/LTB 4 complex formation, consequently inhibiting LTB 4 -BLT1 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to our findings, Griese et al (31) have reported a reduction in airway levels of IL-8 and LTB 4 in individuals with CF treated with aerosolized AAT and suggested the use of AAT outside of the context of AATD. Indeed, the therapeutic potential of AAT in clinical conditions not associated with AATD includes CF, COPD, and RA (71).…”
Section: Discussionmentioning
confidence: 99%
“…AAT protects tissues from proteases released from inflammatory cells. It also exhibits proteaseindependent antiinflammatory activities against these cells and against the soluble effectors they release [176,177] . Unlike immunosuppressive drugs, AAT helps the immune system to disting uish between desired responses against authentic threats and unwanted responses fueled by positive feedback loops [178] , thereby transforming devastating inflammation into beneficial immune tolerance.…”
Section: Controlling Inflammationmentioning
confidence: 99%